npj Antimicrobials and Resistance - Blair, Jessica Mary Alice; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Antimicrobials and Resistance considers basic, applied, and clinical research that advances our understanding of all aspects of antimicrobials and antimicrobial resistance. The journal covers a broad range of topics including but not limited to: Mechanisms of antimicrobial resistance Emerging antimicrobial resistance threats Antimicrobial discovery and development Antimicrobial stewardship and rational use Epidemiology and surveillance Antimicrobials in the environment One Health approaches to antimicrobial resistance Antimicrobial resistance in healthcare settings Community-acquired antimicrobial resistance Veterinary antimicrobial resistance Environmental antimicrobial resistance Innovative therapeutic approaches to combat antimicrobial resistance Global surveillance of antimicrobial resistance Policy and regulatory strategies for addressing antimicrobial resistance The journal offers more choice to Nature Portfolio authors who are seeking a fully open-access and more inclusive platform for publishing their work. The journal is led by microbiology experts who collaborate to cultivate high-quality research. As part of the npj Series, this journal focuses on fostering global partnerships with the research community and other Springer Nature journals.
Keywords: Microbiology; Microbiology